Efek New Normal Terhadap Harga Saham dan Volume Transaksi - Nisya Agustina; Diyah Hariyani; Anny Widiasmara; Tri Jarwa (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2022)
The new normal policy which started on June 1, 2020 provides changes to stock prices and transaction volumes due to the Covid-19 pandemic. This research is directed to see whether there are differences in stock prices and transaction volumes before and during the new normal in the nine IDX industrial sectors. This study uses a quantitative descriptive method with secondary data taken for 60 days before the new normal and 60 days during the new normal then processed with the Wilcoxon Sign Rank test through SPSS 23 software. The data results reveal that there are differences in stock prices before and during the new normal period. in the eight IDX industrial sectors. In the trade, services and investment sectors, there was no difference in stock prices before and during the new normal. The result of transaction volume is that there are differences in transaction volume before and during the new normal period in nine IDX industrial sectors. The difference in stock prices and the volume of transactions that occur increases during the new normal.